One step ahead? The use of foresight by Czech and Slovak non-governmental organizations - Eva Šerá Komlossyová (European Journal of Futures Research, 2020)
Abstract Non-governmental organizations (NGOs) are generally recognized as important actors in societies, fulfilling diverse sets of roles. Given the nature of their work and the complexity of the fast-changing contexts in which they operate, foresight techniques can potentially be useful in helping them prepare for future disruptions and maximize the positive influence of their work over future developments. The possibilities for and benefits of the application of foresight approaches and techniques are increasingly being discussed in various private and public organizations, especially with the aim to innovate and grow. However, little attention has been given to the question of how NGOs use foresight and whether their work benefits from it. The paper presents results of a survey conducted among Czech and Slovak NGOs active in development cooperation, humanitarian assistance, and environmental protection fields, filling the existing research gap by analyzing their application of foresight processes and the benefits foresight brings to them. The paper concludes that future-oriented processes in Czech and Slovak NGOs are of a rather informal and non-institutionalized nature, given the insufficient knowledge of foresight concepts and limited human capacities of NGOs. Nevertheless, they positively influence their creativity and growth.